2015 IEEE International Conference on Communications (ICC) 2015
DOI: 10.1109/icc.2015.7249203
|View full text |Cite
|
Sign up to set email alerts
|

Joint resource allocation and offloading strategies in cloud enabled cellular networks

Abstract: The numerous features installed in recent mobile phones opened the door to a wide range of applications involving localization, storage, photo and video taking and communication. A significant number of applications involve user generated content and require intensive processing which limits dramatically the battery lifetime of featured mobile terminals. Mobile cloud computing has been recently proposed as a promising solution allowing the mobile users to run computing-intensive and energy parsimonious applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(47 citation statements)
references
References 10 publications
0
46
0
1
Order By: Relevance
“…MEC sisteminde offloading veri iletimi yukarda bahsedildiği gibi iki şekilde yapılmaktadır. Çalışma [3]'te ise UE (User Equipment) için uygun bir yürütme gecikmesinde, enerji tüketimini minimize etmek amacıyla bir optimizasyon problemi formüle edilmiştir. Bu optimizasyon problemi Markov chain process min-max aralığında formüle edilmiştir.…”
Section: Offloading Veri İletimiunclassified
“…MEC sisteminde offloading veri iletimi yukarda bahsedildiği gibi iki şekilde yapılmaktadır. Çalışma [3]'te ise UE (User Equipment) için uygun bir yürütme gecikmesinde, enerji tüketimini minimize etmek amacıyla bir optimizasyon problemi formüle edilmiştir. Bu optimizasyon problemi Markov chain process min-max aralığında formüle edilmiştir.…”
Section: Offloading Veri İletimiunclassified
“…Lastly, to obtain an inner convexification for the energy constraint C.2 that satisfies the conditions B1-B6 in Sec. III-B, we utilize the concave-convex structure of the rate function r ul in Q ul as in (18), to rewrite constraint C.2 as…”
Section: B User Schedulingmentioning
confidence: 99%
“…where r ul in + Q ul and r ul in − Q ul −in are given in (18). Using the linearization (19), we then obtain the desired upper bound on C.2 as…”
Section: B User Schedulingmentioning
confidence: 99%
“…The online approach is based on learning from past to find a policy that can cope with unknown environment [9]. In [12], we have studied the online learning approach for our problem and have shown that it is suboptimal in terms of energy consumption due to its imperfect knowledge on the data arrival and the channel state distributions. In this paper, we investigate the offline approach that requires a priori knowledge of the channel statistics and the application properties.…”
Section: Offline Dynamic Programming Strategiesmentioning
confidence: 99%